Legal Analysis of Ijarah-Based Utilization of Waqf Rice Fields: A Case Study of Mosque Waqf Asset Management - Neni Nuraeni; Sumiati (UIN Siber Syekh Nurjati Cirebon, 2026)
This study examines the management of waqf rice fields through an oral ijarah contract at the Nurul Falah Mosque in Bolang Village, Tirtajaya District, Karawang Regency. It aims to analyze the leasing mechanism and assess its validity from the perspectives of Indonesian waqf law and Islamic economic law, particularly regarding contractual validity, evidentiary certainty, asset protection, and the nazhir's administrative responsibilities. The study employed empirical legal research using a qualitative descriptive-analytical approach. Primary data were collected through interviews, observation, and documentation, while secondary data were obtained from legislation, fatwas, books, and relevant scholarly literature. The findings show that the DKM, acting as nazhir, leases the waqf rice fields to local farmers for a specified planting period and rental payment, but the agreement is concluded orally and supported only by limited payment receipts. The arrangement is not automatically invalid because Indonesian waqf law permits cooperation with third parties, and Fatwa DSN-MUI Number 112/DSN-MUI/IX/2017 recognizes oral ijarah agreements when their essential terms are clearly understood. However, the absence of comprehensive written documentation undermines evidentiary certainty and poses governance risks regarding land boundaries, maintenance obligations, agricultural losses, supervision, reporting, and dispute resolution. This study concludes that the practice is substantively permissible but requires written contracts, transparent financial records, periodic supervision, and accountable reporting to strengthen professional waqf governance.